posted by Rachale on .
Help please! I got so far with this and stopped because of confusion. Here is what I have so far.
Let f(x) = 6/x-1 and g(x) = 1 + 3/x find the composite function of (fog)(x)
(fog)(x) = f (g(x))
ok up to
=f (1+3/x) , then
= 6/[1+3/x - 1]
So 2x would be the answer? I was thinking about including the 1+3/x-1 in the middle of the problem... So then 2x is it then I suppose?
It is a good idea to check you final answer by picking some value of x
e.g let x = 3
g(3) = 1+3/3 = 2
then f(g(3)) = f(2) = 6/(2-1) = 6
my expression was f(g(x)) = 2x
then f(g(3)) = 2(3) = 6
Even though this does not "prove" that I have the right answer, there is a very high probability that it is correct.